2014
DOI: 10.1371/journal.pone.0103482
|View full text |Cite|
|
Sign up to set email alerts
|

Galectin-3 as a Marker and Potential Therapeutic Target in Breast Cancer

Abstract: Galectin-3 has a relatively high level of expression in triple-negative breast cancers and is a potential marker for this disease. However, the clinical and prognostic implications of galectin-3 expression in breast cancer remain unclear. We examined mastectomy specimens from 1086 breast cancer cases and matching, adjacent non-cancerous tissues using immunohistochemistry. Overall, triple-negative breast cancers expressed galectin-3 more strongly than did other breast cancers types (63.59% vs 21.36%, P = 0.001)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 24 publications
0
55
1
1
Order By: Relevance
“…In cancer, LEG3 seems to participate to the membrane dynamics of cell migration and in the escaping of the T cells-mediated immune-response [140]. On the basis of its overexpression and of its functions in the breast cancer cells, LEG3 has been recently candidated as biomarker for the triple-negative breast cancer progression [141]. In our tumor samples LEG3, when present, showed a very high expression level, while it was absent in the normal tissues.…”
Section: Galectin Leg3 (Lgals3)mentioning
confidence: 66%
“…In cancer, LEG3 seems to participate to the membrane dynamics of cell migration and in the escaping of the T cells-mediated immune-response [140]. On the basis of its overexpression and of its functions in the breast cancer cells, LEG3 has been recently candidated as biomarker for the triple-negative breast cancer progression [141]. In our tumor samples LEG3, when present, showed a very high expression level, while it was absent in the normal tissues.…”
Section: Galectin Leg3 (Lgals3)mentioning
confidence: 66%
“…Further, to the best of our knowledge, we identify collagen XII for the first time as elevated during post-weaning mammary involution. Importantly, potential roles for each of these highlighted ECM proteins in breast cancer metastasis have been elucidated, with the exception of collagen XII (6770). While collagen XII has been shown to be upregulated in malignant breast cancer cell lines, and has been identified as a prognostic marker in other cancers, its role in breast cancer progression has yet to be established (71, 72).…”
Section: Discussionmentioning
confidence: 99%
“…The attenuation of galectin-1 suppressed metastasis in a 4 T1 mouse xenograft breast cancer model [14] and tumor growth in a lung cancer model [16], and also prolonged the survival of glioma-bearing mice [17]. Increased galectin-3 expression has been shown to be associated with the poor prognosis of hepatocellular carcinoma [18], metastasis of renal cell carcinoma [19] and chemoresistance of breast cancer [20]. By contrast, other studies have shown that galectin-3 expression is positively correlated with a favorable prognosis in neuroblastic tumors [21], and the reduction of galectin-3 expression at the invasive front is associated with the invasion and metastasis of colorectal carcinoma [22].…”
Section: Introductionmentioning
confidence: 99%